Tindak Pidana Penyelundupan Manusia Dengan Modus Operandi Memperkerjakan PMI Ke Luar Negeri Ditinjau Dari UNCATOC Dan Hukum Internasional - Dikky Firsthio Damas; Fabian Bagaskara Sugianto; Randy Asmoro Dwi Purnomo (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
People smuggling affects all regions of the world. Every year, thousands of immigrants and refugees try to leave their home countries and seek a better life in their destination countries. The purpose of this paper is to find out how the criminal act of people smuggling with the modus operandi of employing PMIs abroad in terms of UNCATOC and international law and what is the relationship between the crime of human smuggling and international migration if it is associated with international law. It can be concluded that the United Nations Convention against Transnational Organized Crime has a Protocol that is intended to combat smuggling by preventing, investigating and prosecuting violations, and by promoting international cooperation among States Parties to protect the human rights and other interests of smuggle.